A decision support system for air cargo warehouse design - Karaismailoğlu, Adnan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Warehouse design is critical in the air cargo industry, where the service standards are high and the competition is getting harder. The designers of air cargo warehouses consider various criteria like costs, system failure risks, customer perception and marketing power to evc::Huate the alternative designs and find the optimal one. The issue of designing an air cargo warehouse is generally considered by design and consulting companies, which provide a broad experience in operational design but they lack in suggesting different alternatives based on a theoretical framework. The alternative warehouse designs are generated by allowing different combinations of resource capacities such as the number of gates, workstations and storage areas. The evaluation of these alternative designs requires the use of analytical methodologies for multi criteria decision making. At this point, simulation which is a popular tool to evaluate the operational performances and Analytical Hierarchy Process (AHP) which provides the ability to evaluate in accordance to qualitative as well as quantitative criteria, appear to be the common tools used in the literature for such problems. In this study, a flexible and user-friendly Decision Support System (DSS) is developed based on simulation and AHP approaches. The DSS is used to generate design alternatives, evaluate their performances, rank them according to a set of decision criteria and report the results. The graphical interfaces are designed in accordance with the consideration of the man-machine interaction to increase its functionality. The environment is applied with real-time data in one of the Europe's biggest air cargo carriers and the findings are discussed.
Keywords: Warehouses -- Design and construction.; Warehouses -- Automation.; Aeronautics, Commercial .